2021
DOI: 10.3389/fpsyt.2021.746330
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Parents and Preschool-Aged Children During the COVID-19 Pandemic: The Mediating Role of Harsh Parenting and Child Sleep Disturbances

Abstract: In the context of the coronavirus disease-2019 (COVID-19) pandemic, mental health problems of parents and children have become a public issue. Herein, we explored the association between parental well-being index and child mental health problems during the pandemic and the mediating role of harsh parenting and child sleep disturbances. An online survey was conducted among 16,398 parents of children aged 3–6 years (48.1% girls, Mage = 4.69 years, SDage = 0.75 years) from March 15 to 29, 2020. Child mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…Of the 30 included studies, about one-third explored the association between sleep and children's mental health during COVID-19 ( 32 , 43 , 47 , 48 , 50 , 55 , 58 , 61 , 63 , 67 ). With the closure of schools, home confinement and social isolation which led to significant changes in children's daily routines and activity patterns, children's sleeping patterns, such as sleep timing (delayed bedtime and rise time) and quality, were altered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 30 included studies, about one-third explored the association between sleep and children's mental health during COVID-19 ( 32 , 43 , 47 , 48 , 50 , 55 , 58 , 61 , 63 , 67 ). With the closure of schools, home confinement and social isolation which led to significant changes in children's daily routines and activity patterns, children's sleeping patterns, such as sleep timing (delayed bedtime and rise time) and quality, were altered.…”
Section: Resultsmentioning
confidence: 99%
“…Since children were forced to stay at home due to school closures and home confinement, the limited space at home as well as the restricted outdoor opportunities for children to be physically active were drastically reduced ( 70 ). Of the 30 included studies, eight studies ( 50 , 55 , 56 , 58 , 60 , 61 , 63 , 67 ) examined the relations between physical activity and children's internalizing or externalizing behaviors. In an internet-based survey of 1,264 children, Liu et al ( 56 ) found that when compared with children who did not do any physical activity, children with physical activity had a lower risk of hyperactivity-inattention (OR 0.44 for 1–2 days/week; OR 0.56 for more than 2 days/week) and fewer prosocial behavior problems (OR 0.65 for 1–2 days/week; OR 0.55 for more than 2 days/week).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic parental mental health problems consequentially lead to harsh parenting experiences, aberrant interpersonal relationships and increased stress levels which incrementally and cumulatively affect the child [ 110 ]. Wang et al [ 135 ] report that poor parental mental health has significant impact on their parenting styles with significant repercussions on their children’s mental health. Depression is closely associated with neglectful parenting [ 40 ].…”
Section: Ineffective Parenting and Its Triggersmentioning
confidence: 99%